Hematology and oncology clinical care during the coronavirus disease 2019 pandemic. (14th July 2020) - Shah, Manish A.; Emlen, M. Frances; Shore, Tsiporah; Mayer, Sebastian; Leonard, John P.; Rossi, Adriana; Martin, Peter; Ritchie, Ellen; Niesvizky, Ruben; Pastore, Raymond; Cigler, Tessa; De Sancho, Maria; et al.
Abstract: New York City has been at the epicenter of the coronavirus disease 2019 (COVID‐19) pandemic that has already infected over a million people and resulted in more than 70, 000 deaths as of early May 2020 in the United States alone. This rapid and enormous influx of patients into the health care system has had profound effects on all aspects of health care, including the care of patients with cancer. In this report, the authors highlight the transformation they underwent within the Division of Hematology and Medical Oncology as they prepared for the COVID‐19 crisis in New York City. Under stressful and uncertain conditions, some of the many changes they enacted within their division included developing a regular line of communication among division leaders to ensure the development and implementation of a restructuring strategy, completely reconfiguring the inpatient and outpatient units, rapidly developing the ability to perform telemedicine video visits, and creating new COVID–rule‐out and COVID‐positive clinics for their patients. These changes allowed them to manage the storm while minimizing the disruption of important continuity of care to their patients with cancer. The authors hope that their experiences will be helpful to other oncology practices about to experience their own individual COVID‐19 crises.